FIRST LANGUAGE ACQUISITION OF THE DIGITAL GENERATION - Nemin Kaharuddin, Mutahharah; Rismayanti, Rismayanti; Pammuda, Pammuda; Rengko, Sumarlin (JURNAL KONFIKS, 2026)
This study aims to analyze the process of first language acquisition in children of the digital generation through a comprehensive psycholinguistic approach. The method used is qualitative descriptive, with data collected through in-depth interview techniques, systematic listening observation, recording of interactions, and detailed note-taking of a four-year-old child as the research subject. The focus of the analysis is directed at the forms of language acquisition as well as the categories of word classes used by the subject in the context of daily interactions. The research results reveal that the child’s first language acquisition involves two languages, namely Indonesian and English, demonstrating characteristics of early bilingualism developing simultaneously. The vocabulary acquired includes various categories of word classes, such as verbs, nouns, adjectives, and numerals, reflecting the variety and complexity of the language mastered by the child. Intensive exposure to the digital environment, such as the use of interactive digital media and bilingual content, is suspected to play a significant role in fostering the development of bilingual abilities in children from an early age. These findings illustrate that interaction with digital media and bilingual content not only enriches the child’s vocabulary but also accelerates the process of first language acquisition within an increasingly complex and dynamic social context. This study also emphasizes the importance of psycholinguistic studies in understanding the dynamics of language acquisition among generations growing up in the digital era, as well as its implications for the development of adaptive language learning strategies that meet the needs of today’s children. Thus, this study makes a significant contribution to understanding how the digital environment influences first language development and bilingualism in preschool-aged children.